Charles Francis Hall (1821-1871) - Loomis, Chauncey (ARCTIC, 1982)
Hall conceived an interest in arctic exploration in his late thirties and in 1859 he mounted his first expedition in search of Franklin. He sailed to Baffin Island on board a whaling vessel and was fortunate to encounter an English-speaking Eskimo couple when he was put on shore. They taught him about arctic survival and were his loyal companions throughout his life. His next trip north was made in 1865. This time the whaling vessel put him ashore at Roe's Welcome Sound in Hudson's Bay. In 1869 he finally reached King William Island where he found relics from the Franklin Expedition, but gave up hope of finding any survivors. In 1871 he sailed north as leader of a full-scale expedition, aboard the Polaris. He and the leader of the scientific staff, Dr. Emil Bessels, shared very poor relations, and once the ship and crew had settled for the winter in Hall Basin, Hall briefly travelled by sledge northwards, returned to the ship, and after drinking a cup of coffee became violently ill. He died two weeks later. His body was exhumed in 1968 by Chauncey Loomis, Hall's biographer. An autopsy revealed that Hall had been given large doses of arsenic, which was commonly used as a medicine, prior to his death. It is not known whether Dr. Bessels did this, accidentally or otherwise, or the arsenic was self-administered. However, Dr. Bessels never admitted to the Board of enquiry that he administered any arsenic to Charles Hall.